Dampak Gejolak Politik Demonstrasi 2025 Terhadap Volatilitas IHSG Sektor Perbankan dan Nilai Tukar Rupiah - Doretia Deriana Ina Kii; Hendrik Suhendri; Yayuk Sulistiyowati (Yayasan Lentera Avanya Nagari, 2026)
This study aims to analyze the effect of political turmoil in the form of the 2025 demonstrations on the volatility of the Composite Stock Price Index (CSPI) and the Rupiah exchange rate in the banking sector in Indonesia. The study employs a quantitative approach using the event study method and volatility analysis. The research data consist of secondary data obtained from the Indonesia Stock Exchange, Yahoo Finance, and Bank Indonesia, with an observation period of five days during the demonstrations and five days after the 2025 demonstrations. The research sample consists of six state-owned banks selected using purposive sampling techniques. Data analysis was conducted using a paired sample t-test to examine differences in CSPI volatility and the Rupiah exchange rate before and after the demonstration events. The results indicate that the 2025 demonstrations had a significant effect on CSPI volatility and the Rupiah exchange rate. Statistical test results show a significant difference between the period during and after the demonstrations, with a significance value of 0.000 < 0.05. These findings indicate that political turmoil can affect capital market stability and macroeconomic conditions, particularly in the banking sector, which is sensitive to political and economic changes. This study supports signaling theory and semi-strong form market efficiency theory, which state that political information serves as a signal for investors in making investment decisions.